Biosimilar recombinant follicle stimulating hormones in infertility treatment. (October 2014) - Santi, Daniele; Simoni, Manuela
<x xml:space="preserve">Abstract</x> Introduction: Follicle stimulating hormone (FSH) is a glycoprotein hormone essential for reproduction both in females and males and it is physiologically produced by the anterior pituitary gland in several isoforms. This heterogeneity is typical also of FSH-containing compounds, both urinary-derived and recombinant products. These compounds are widely used in assisted reproductive technologies (ART), to induce multifollicular development. Recently, the increased cost pressure on healthcare systems and the patent expiration date of widely used biotechnology-derived, recombinant FSH, prompted the pharmaceutical interest in FSH biosimilars. Areas covered: In 2014, two FSH biosimilars obtained marketing authorization by the European Medicines Agency. Here, we review the biology of natural, extractive and recombinant FSH, the current state of biosimilar FSH, including the legal framework, and aspects to be considered in biosimilar FSH usage. Literature search methodologies included Medline and PubMed research. Expert opinion: Biosimilar FSH preparations are expected to be biologically and clinically 'non inferior' to the originator product. However, the impact of FSH biosimilars on cost and outcomes of ART is far from being established, since insufficient information is available to demonstrate the pros and cons in the long-term application.